The Activity of Purple Sweet Potato Leaves (Ipomea batatas Ver.) Extract to Calcium Oxalate Concentration of Male Rat (Rattus novergicus) - Roihatul Mutiah; Avin Ainur Fitrianingsih; Yen Yen Ari Indrawijaya; Nabila Rahmadani (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Purple sweet potato leaves (Ipomea batatas Ver.) has been proven to have anti-lithiasis effects in vitro in treating kidney stone disease. This is due to the high content of potassium in the leaves. The study aimed to analyze the effect of purple sweet potato leaf extract on kidney stone decay in male white rats induced by ethylene glycol 0.75% and ammonium chloride 2% for 10 days. In this study, 24 mice were divided into 6 groups: normal or without induction group, positive control, negative control, dose group 300 mg/200-gram body weight, 400 mg/200-gram body weight, and 500 mg/200-gram body weight. The parameters observed were calcium levels in the urine tested using Atomic Absorption Spectrophotometry, oxalate levels in urine tested using UV VIS Spectrophotometer. The results of this study indicate that purple sweet potato leaf extract at a dose of 500 mg/200-gram body weight can increase the levels of calcium and oxalate in the urine of rats compared with negative controls.